Socialization of the Scope of Cybercrime Occurring in the Community in the Area of RT 007 RW 018, Kedaung Subdistrict, Pamulang District, South Tangerang City, Banten Province - Martahan Siburian (Yayasan Daarul Huda Kruengmane, 2026)
The use of information technology, media, and communication has made a person's behavior better in behaving in a society. The development of information and communication technology has also caused world relations to be unhindered by existing boundaries and norms so that it can cause changes in all fields, such as social, economic and cultural fields, quickly and widely. Information technology is currently a double-edged sword because in addition to contributing to the improvement of welfare, progress, and human civilization, it is also an important factor in unlawful acts. This change also has a huge impact on the transformation of values in society. The impact caused by technological development is not only a positive impact but there is a negative impact, the development of technology that is used for crimes commonly known as cybercrime. Cybercrime refers to criminal activities with computers or computer networks that become tools or places of crime. Some examples of cybercrime include hacking, cracking, defacing, etc. Likewise, ATM break-ins, online gambling, and pornography are included in computer crime.